Audit of cesarean section by non-obstetricians in the remote part of Nepal using the Robson classification system - Ghimire, Rajan; Rai, Tupesh Thulung; Dhamala, Manoj; Adhikari, Sugat (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Cesarean delivery is increasing throughout the globe. It is increasing here in Nepal too. There are inequalities in cesarean deliveries in urban and rural/remote areas. Through this study, we tried to see the Cesarean delivery rate in one of the remote districts of Nepal and audited the Cesarean deliveries as per the Robson classification system.Method: A retrospective cross-sectional study based on secondary data collection of sixteen months (Aug 2019 to Dec 2020) was designed for this purpose. We collected data from the health management and information system (HMIS) maternity registry and record files of inpatients located in District Hospital, Terhathum. We used the Robson classification system and Robson reporting table for the analysis purpose.Result: We included 495 participants. The overall Cesarean rate was 12.9%. Robson group 1 i.e. nulliparous, single, cephalic, >37 weeks of gestation contributed most (40.63%) in cesarean delivery followed by group 5 (17.19%) i.e. multiparous, single, cephalic, >37 weeks of gestation with previous Cesarean section (CS).Conclusion: In our study, the main contributor to CS was Robson group 1 i.e. nulliparous, single, cephalic >37 weeks of gestation followed by group 5 i.e. multiparous, single, cephalic >37 weeks of gestation with previous CS. Though the CS rate is within the WHO recommendation, we need to intervene to decrease CS in low-risk groups and strengthen hospital facilities for vaginal birth after Cesarean (VBAC).